Gambaran Kematangan Psikologis pada Calon Pengantin Aparatur Sipil Negara (ASN) di Kota Surakarta, Jawa Tengah - Putri Wulansari; Sri Ernawati; Dhian Rizkiana Putri (Pusat Riset dan Inovasi Nasional, 2025)
Marriage is a crucial phase in an individual's life cycle that requires comprehensive readiness, particularly in terms of psychological maturity. Psychological maturity reflects a person's ability to manage emotions, think rationally, and establish mature interpersonal relationships—factors that are fundamental in building a harmonious and sustainable family. This study aims to describe the level of psychological maturity among prospective brides and grooms who work as Civil Servants (Aparatur Sipil Negara/ASN) in the city of Surakarta, Indonesia. This research employs a descriptive qualitative approach, using data collection techniques such as observation, in-depth interviews, and documentation. The subjects of the study consist of six civil servant couples preparing for marriage and one supporting informant from the Regional Civil Service and Human Resource Development Agency (BKPSDM), who acts as their institutional supervisor. The data were analyzed thematically using an inductive approach. The findings reveal varying levels of psychological maturity among the prospective civil servant brides and grooms. Some individuals demonstrate emotional and cognitive readiness, while others are still struggling to cope with the transition into married life. Contributing factors include personality traits, educational background, religious values, family upbringing, and social environmental pressure. Most participants exhibit positive indicators such as effective communication skills, a sense of responsibility in relationships, and a willingness to continue learning. However, a few still face psychological challenges, such as anxiety caused by societal expectations or familial pressure to marry soon. Pre-marital counseling programs provided by BKPSDM have proven to be effective in equipping these individuals with psychological, spiritual, and educational support, thereby enhancing their readiness for marriage. These programs also foster a deeper understanding of marital roles and emotional preparedness in dealing with potential conflicts. In conclusion, although the levels of psychological maturity vary, most prospective civil servant couples in Surakarta possess a sufficient foundation to establish a healthy family. However, continued intervention through therapy or guidance is recommended for those who are not yet fully prepared psychologically.